Oral vaccination of mice with attenuated Salmonella encoding Trichinella spiralis calreticulin and serine protease 1.1 confers protective immunity in BALB/c mice. - Sheng Jie Bai; Lu Lu Han; Ruo Dan Liu; Shao Rong Long; Xi Zhang; Jing Cui; Zhong Quan Wang (Public Library of Science (PLoS), 2022)
Background Trichinella spiralis is a foodborne parasitic nematode which is a serious risk to meat safety. Development of anti-Trichinella vaccine is needed to control Trichinella infection in food animals. In this study, two novel T. spiralis genes (calreticulin and serine protease 1.1) in combination were used to construct oral DNA vaccines, and their induced protective immunity was evaluated in a murine model. Methodology/principal findings TsCRT+TsSP1.1, TsCRT and TsSP1.1 DNA were transformed into attenuated Salmonella typhimurium ΔcyaSL1344. Oral vaccination of mice with TsCRT+TsSP1.1, TsCRT and TsSP1.1 DNA vaccines elicited a gut local mucosal sIgA response and systemic Th1/Th2 mixed response. Oral vaccination with TsCRT+TsSP1.1 induced obviously higher level of serum specific antibodies, mucosal sIgA and cellular immune response than either of single TsCRT or TsSP1.1 DNA vaccination. Oral vaccination of mice with TsCRT+TsSP1.1 exhibited a 53.4% reduction of enteral adult worms and a 46.05% reduction of muscle larvae, conferred a higher immune protection than either of individual TsCRT (44.28 and 42.46%) or TsSP1.1 DNA vaccine (35.43 and 29.29%) alone. Oral vaccination with TsCRT+TsSP1.1, TsCRT and TsSP1.1 also obviously ameliorated inflammation of intestinal mucosa and skeletal muscles of vaccinated mice after challenge. Conclusions TsCRT and TsSP1.1 might be regarded the novel potential targets for anti-Trichinella vaccines. Attenuated Salmonella-delivered DNA vaccine provided a prospective approach to control T. spiralis infection in food animals.